Management of Digital Communications with Target Groups by Leading Russian Universities - E. V. Brodovskaya; A. Yu. Dombrovskaya; V. A. Lukushin (Высшее образование в России)
The article presents the results of an empirical study on the assessment of digital communications management with target groups of Russian universities in social media. A sample of universities is based on the «QS World University Ranking by Subjects 2021: Social Sciences and Management 2021». Among the cases of applied research: National Research University «Higher School of Economics», Russian University of Economics, Financial University under the Government of the Russian Federation, Russian Academy of National Economy and Public Administration under the President of the Russian Federation, MGIMO University, Peoples’ Friendship University of Russia. The results of a comparative analysis has been carried out using the method of graph with the use of a special software based on determining the structural links of the most significant digital communities of selected universities, as well as social media analysis aimed at determining the key parameters of user activity. The method proposed by the authors makes it possible to assess the scale and nature of communication between universities and selected target groups. Based on the data obtained, we have developed recommendations for improving the digital management of universities, increasing the density of connections and the integration of users within the online communities of universities as one of the conditions for effective management of a university brand in the modern network space.